Uneven stigma loads: Community interpretations of public health policies, ‘evidence’ and inequities in shaping Covid-19 stigma in Vietnam - Duy Hoang Trinh; Shannon McKinn; Anh Thuy Nguyen; Greg J. Fox; Anh Thu Nguyen; Sarah Bernays (SSM: Population Health, 2022)
The infectious spread of COVID-19 has been accompanied by stigma in both global and local contexts, sparking concern about its negative effect on individuals, communities, and public health responses. The changing epidemiological context of the COVID-19 epidemic and evolving public health responses during the first year of the pandemic (2020) in Vietnam serve as a case study to qualitatively explore the fluidity of stigma.We conducted in-depth interviews with 38 individuals, (13 cases, 9 close contacts, and 16 community members) from areas affected by local outbreaks. Thematic analysis was conducted iteratively.Our analysis indicates that the extent and impacts of COVID-19-related stigma were uneven. Adapting the clinical term 'viral load' as a metaphor, we describe this variation through the wide range of 'stigma load' noted in participants' experiences. Individuals encountering more acute stigma, i.e. the highest 'stigma load', were those associated with COVID-19 at the start of the local outbreaks. These intensively negative social responses were driven by a social meaning-making process that misappropriated an inaccurate understanding of epidemiological logic. Specifically, contact tracing was presumed within the public consciousness to indicate linear blame, with individuals falsely considered to have engaged in 'transgressive mobility', with onward transmission perceived as being intentional. In contrast, as case numbers grew within an outbreak the imagined linearity of the infection chain was disrupted and lower levels of stigma were experienced, with COVID-19 transmission and association reframed as reflecting an environmental rather than behavioural risk.Our findings demonstrate the role of public health policies in unintentionally creating conditions for stigma to flourish. However, this is fluid. The social perceptions of infection risk shifted from being individualised to environmental, suggesting that stigma can be modified and mitigated through attending to the productive social lives of public health approaches and policies.